Peningkatan Tingkat Kesadaran Masyarakat dalam Melakukan Terapi Latihan Active Exercise dalam Mencegah Terjadinya Kondisi Myofascial Pain Syndrome - Syurrahmi Syurrahmi; Lilik Sigit Wibisono; Zamroni Zamroni; Gresyla Putri Karunia (Lembaga Pengembangan Kinerja Dosen, 2025)
Myofascial pain syndrome (MPS) is a condition characterized by muscle or fascia pain, involving sensory, motor, or autonomic functions, linked to myofascial trigger points (MTrPs). Motor symptoms can include muscle weakness, limited movement, and stiffness. Sensory symptoms may involve tenderness, referred pain, hyperalgesia, or allodynia, while autonomic symptoms include sweating, changes in skin temperature, and salivation. MPS occurs due to increased sympathetic nervous system activity, which worsens pain. Physical therapy is vital in improving movement and function, with Active Exercise Therapy being a recommended treatment. MPS affects 36% of 431 patients, with pain intensity often developing within a week, and in Indonesia, it reaches 40% within a year. MPS is more common in females than males. Active Exercise Therapy, which can be performed at home or work, is essential for preventing MPS. On July 31, 2025, a community service activity was held at RT VIII Tanjung Mas Village, Semarang Utara, with 29 participants. The event included blood pressure checks, blood sugar tests, BMI measurements, and counseling on the importance of exercise therapy to prevent muscle fatigue, particularly in the neck area. The therapy, focusing on improving tendon and ligament strength and muscle strength, helps maintain joint stability and increase the range of motion. Strength training includes isotonic exercises and progressive resistance training, tailored to each individual's needs. The event provided education on managing muscle pain and fatigue through targeted exercise routines and home programs. These initiatives emphasize muscle recovery, physical health, and overall wellness, ensuring participants can manage and prevent MPS effectively. The event highlighted the critical role of regular physical activity in improving quality of life and preventing long-term musculoskeletal pain.